Dementia-linked amyloidosis is associated with brain protein deamidation as revealed by proteomic profiling of human brain tissues - Adav, Sunil S. (2016)
Background: Aggregation of malformed proteins is a key feature of many neurodegenerative diseases, but the mechanisms that drive proteinopathy in the brain are poorly understood. We aimed to characterize aggregated proteins in human brain tissues affected by dementia.